SIMBOL KOMUNIKASI DAKWAH MELALUI SENI HADRAH AL-ANSHOR DI KALIDAMI SURABAYA (KAJIAN KOMUNIKASI BUDAYA HADRAH AL ANSHOR DI KALIDAMI – SURABAYA) - Alhasani, Ahmad Abdul Rozak; Rochim, Achludin Ibnu; Hamim, Hamim (representamen, 2018)
The situation in 1996 in Kalidami – Surabaya at that time a negative thingshappens like gets drunk, a gambling, and fights between the teenager, and it’s trigger theinteraction of local citizens to hold a positive activity in order to cope within. ThePresence of Hadrah activities by Al – Anshor groups at that time, can be said as theoccurrence of ' symbolic Interaction ' where hadrah musical itself became the symbolicthat agreed in a group and used to reach a common ground to shared meanings thatisreduce the bad things that happen in Kalidami.The interactions that occur within the group itself and outside groups bringingimprovements impact to the mindset of individual especially teenagers in Kalidami to getbetter understanding in Islamic religion through preaching and discussions thatpresented in their activity, its encourage significant changes and form the character ofeach self becomes better and realize to avoid having bad behavior. This symbolicInteraction applied using 2 Communications i.e., verbal and non verbal communication,so the preaching about religion is acceptable to the local community because theyapproach without affecting the local culture.Keywords : Communication, Propaganda, Hadroh, Symbolic Interaction, Culture.